Relationships of Natural Enemies and Non-prey Foods - Lundgren, Jonathan G. (Progress in Biological Control, 2009)
There are very few natural enemies so maladapted as to rely on prey as their sole nutritional resource. The importance of non-prey sources of nutrition have received disproportionately less attention than prey when one considers how important non-prey foods are to the evolution and ecology of natural enemies. This book examines the intricate and diverse interactions between non-prey foods and natural enemies from both parties' perspectives, beginning at an organismal level and taking the reader on a journey that illustrates how these interactions are inextricably tied to the outcome of biological control programs targeting insects and weed seeds.